Effect of Energy Gain and Loss in Breathing Pattern of Solitary Wave for Nonlinear Equation - Nur Shafika Abel Razali; Farah Aini Abdullah; Yahya Abu Hasan; Agus Suryanto (Journal of Natural A, 2014)
Nonlinear phenomena like soliton propagate over long distance in transmit information, without dispersion energy due to the properties of the solitons, which has balanced of the nonlinearity effect and dispersion effect resulted the signal undistorted and symmetric bell shape curve. We study about the properties and breathing pattern of solitary wave of pulses in absence and present of energy loss, by using one dimensional nonlinear equation; cubic-quintic complex Ginzburg-Landau equation (cqCGLE). Breathing pattern of soliton behaviour is constructed with hyperbolic sine and hyperbolic tangent as initial amplitude profile and observed by means of numerical simulation. Resulting in observation of breathing pattern of soliton in term of energy loss and gain while travelling, but it still maintains spatial localization of wave energy in the changing pulses shape through a unique dissipative soliton.Keywords— Soliton, nonlinearity, dispersion, breathing, energy.